Red blood cells from the South American rattlesnake (Crotalus durissus terrificus) regulate volume incompletely following osmotic shrinkage and swelling in vitro - Koldkjaer, P.; Wang, T.; Taylor, T. W.; Abe, Augusto Shinya [UNESP] (Elsevier B.V., 2000)
The ability of rattlesnake (Crotalus durissus terrificus) red blood cells to volume regulate in vitro has been investigated. Blood was drawn through a catheter inserted in the dorsal aorta and equilibrated to gas mixtures of different composition. Cells shrunken osmotically by increasing the extracellular osmolarity from approximate to 291 mosm l(-1) (n = 3) to approximate to 632 mosm l(-1) (calculated) only partially regulated their volume back towards the original volume either at pH 7.51 +/- 0.05 (mean +/- S.D., n = 5) or pH 7.20 +/- 0.06 (mean +/- S.D., n = 3), There was no improvement of the regulatory volume increase at low haemoglobin oxygen saturation. The limited volume restoration was inhibited by separate additions of amiloride (10(-4) M) or DIDS (10(-4) M) suggesting involvement of the Na+/H+ and Cl-/HCO3- exchangers. Cells that were swollen osmotically by an approximate to 30% dilution of the extracellular medium also exhibited a limited ability to recover their volume. Therefore, these cells show little ability to volume regulate when exposed to in vitro conditions that shrink or swell the cell. (C) 2000 Elsevier B.V. All rights reserved.
Keywords: reptile; snake; Crotalus durissus; red blood cell; volume regulation; osmotic swelling; osmotic shrinkage; effects of oxygenation